Economic and Spatial Regional Integration and Its Impacts on Regional Development in North Tapanuli Regency - Sugiarto, Abdi; Kustiah Ramadania, Rini (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
This research aimed to analyze and understand the impact of Economic and Spatial Regional Integration on Regional Development in North Tapanuli Regency. The data collection technique involved indirect observation, which included reading, collecting, and noting data, information, and their descriptions. The type of data used in this research was quantitative data in the form of secondary time series data. The data included Gross Regional Domestic Product (GRDP) data, geographic data, population figures, distances between regions, regional potential, and other data, sourced from the Central Statistics Agency (BPS) of North Sumatra Province, BPS and Regional Development Planning Agency (BAPPEDA) of North Tapanuli Regency, as well as online sources. The results of the analysis depict substantial GRDP growth and growth rates in both sub-districts: Siborong borong Sub-district with an index value of 184,495,189 and Simangumban Sub-district with an index value of 19,632,902. The analysis also demonstrated consistent and integrated growth across each sub-district and the regency in North Tapanuli. The Gravity Model revealed that North Tapanuli Regency had a strong attraction to its supporting areas, influenced by distance and interactions. The Williamson Index measures income inequality between regions, with results nearing 0, indicating economic equalization between the growth center and its supporting areas. In regional development, the role of North Tapanuli Regency as a growth center contributes to driving economic growth and the welfare of the surrounding communities.